Peran Guru sebagai Role Model dalam Membina Akhlak Siswa SUPM Ladong Aceh - Muhammad Syauqi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Teachers have a duty to educate, in a broad sense, which refers to teaching, giving encouragement or motivation, praising, punishing, role-modeling, developing habits, and others. In the process of education, an educator is expected to have good teaching skills, high pedagogic competence, a good personality, and exemplary attitudes. In this study, the focuses were on the teachers’ roles as role models in fostering students’ behaviors, the obstacles faced by teachers as role models in fostering the students’ behaviors, and the efforts made to overcome the obstacles faced by the teacher as a role model in fostering the students’ behaviors at SUPM Ladong Aceh. The study used a qualitative approach, taking a total of 10 respondents, consisting of the school principal, the teachers, and the students of SUPM Ladong Aceh. Data were collected through observation, interview, and documentation. The results of the study showed that the teachers of Islamic religious education have played a very important and strategic role in building the students’ characters. The teachers have tried to act as mentors, advisors, role models, and evaluators for the students. In terms of the obstacles, the teachers encountered the lack of self-awareness of exemplary behaviors needed in developing the students’ behaviors, the students’ lack of awareness of the importance of moral education for everyday life, and the environmental factors that influenced the students. To overcome these issues, the teachers kept showing exemplary attitudes, educating the students through applying supervision policy and counseling, teaching good habits to the students, giving rewards and punishments, disciplining the students, and working together with the parents, as well as applying the curriculum of moral education explicitly.